No pain, no strain: Targin® mitigates pain and constipation following spinal cord injury. Issue 3 (24th January 2023) - Sachdeva, Rahul; Hosseinzadeh, Ali; Rizzardo, Aaron; Maharaj, Andrea; Berger, Michael; Krassioukov, Andrei
Abstract: Background: Opioids effectively reduce chronic pain, but present significant side effects including opioid‐induced constipation. Oxycodone/naloxone decreases pain and constipation in cancer patients, however its effect on spinal cord injury population remains understudied. Methods: We assessed whether oxycodone/naloxone reduces pain, constipation, and severity of autonomic dysreflexia in an individual with spinal cord injury. A 55‐year‐old male with C5 lesion presented with chief complaint of chronic pain received 5/2.5 mg and 20/10 mg oxycodone/naloxone for 6 and 2 weeks, respectively. Results: Oxycodone/naloxone improved pain, bowel function, and autonomic dysreflexia severity. Interpretation: Oxycodone/naloxone was effective in managing chronic pain and constipation in the studied case.